Kegiatan preservasi bahan pustaka di Diperpuska Ciamis - Bagas Agung Pratama; Evi Nursanti Rukmana (Faculty of Communication, Padjadjaran University, 2023)
Preservation research at the Dinas Perpustakaan dan Kearsipan Kabupaten (Diperpuska) of Ciamis is needed to increase understanding of preservation activities and the methods used. To identify challenges and limitations faced to increase the effectiveness of the preservation process and realize the important role of preservation in maintaining the sustainable use of library collections. This study aims to explore preservation activities carried out by the Diperpuska of Ciamis. Research method used was a qualitative descriptive method which includes interviews, literature studies, and observations. Data analysis using interactive model data analysis techniques. The results showed that the Diperpuska of Ciamis carried out library material preservation activities through preventive activities by conducting collection education, environmental regulations, prohibitions and sanctions, as well as collection control and security. Then curative activities by carrying out periodic cleaning, weeding, maintenance, and fumigation. Finally, restorative activities by binding to library materials that have been damaged. Preservation activities carried out by the Diperpuska of Ciamis are to ensure that library materials can still meet the needs of the community in the Ciamis Regency area. Damage to library materials can be caused by internal and external factors. There are several obstacles in carrying out preservation activities such as the lack of supporting tools, special rooms, and human resources. It was concluded that preservation activities had been carried out by the Diperpuska of Ciamis by carrying out preventive, curative and fumigation activities and required additional facilities and professional staff so that preservation activities could be carried out more optimally.